2016
DOI: 10.1590/0103-8478cr20150396
|View full text |Cite
|
Sign up to set email alerts
|

Performance and meat chemical composition of quails fed with different sorghum levels instead of corn

Abstract: Performance and meat chemical composition of quails fed with different sorghum levels instead of corn.Ciência Rural, v.46, n.5, mai, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…4). This is consistent with other studies that reported similar chemical composition of meat in broiler chickens fed sorghum (whole grain or ground) that replaced partially or totally corn (Garcia et al, 2005;Carolino et al, 2014) or in meat-type quail (Moraes et al, 2016). Comparing three nutritional programs with whole sorghum grain-based diets in Hubbard broilers, Silveira et al (2017) reported values to range from 23.39-23.66% for protein and from 2.6-2.68% for fat contents of breast meat.…”
Section: Resultssupporting
confidence: 92%
“…4). This is consistent with other studies that reported similar chemical composition of meat in broiler chickens fed sorghum (whole grain or ground) that replaced partially or totally corn (Garcia et al, 2005;Carolino et al, 2014) or in meat-type quail (Moraes et al, 2016). Comparing three nutritional programs with whole sorghum grain-based diets in Hubbard broilers, Silveira et al (2017) reported values to range from 23.39-23.66% for protein and from 2.6-2.68% for fat contents of breast meat.…”
Section: Resultssupporting
confidence: 92%
“…Quail production has been increasing in recent years because of the potential for meat production, high egg production, commercial diversity and fast return on investment. Studies in the field of quail nutrition have focussed on specific topics, such as nutritional protein, energy and amino-acid requirements (Moraes et al 2016). However, data on pigment agents and alternative foods and their effect on metabolism are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The sorghum, increasingly, have been used in poultry feed formulations as an alternative ingredient to corn. Research results show the possibility of replacing up to 100% of corn by sorghum without causing damages on poultries performance (FAGUNDES et al, 2017;MORAES et al, 2016;SALEH et al, 2019). However, the use of sorghum causes a decrease in pigmentation of the meat and egg yolk of the birds (MOURA et al, 2010;SOUZA et al, 2015;SOUZA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%